Extra-regional aspects of Uruguay’s foreign policy (2010-2015 - Irina Kireeva (Ибероамериканские тетради)
The article analyses extraregional aspects of Uruguay’s foreign policy during the presidency of José Mujica (2010-2015), namely the development of relations between Uruguay and the USA, the European Union, Russia and countries of Asia and Middle East such as China, India, Iran, Palestine and Israel. This aspect of Uruguayan foreign policy is particularly relevant amid the crisis in Mercosur, when Uruguay is trying to mitigate its adverse consequences for the country’s economy by expanding trade ties with the other countries, both within Latin America and beyond it. The relations between Uruguay and Latin American countries are touched upon in some investigations while Uruguay’s active foreign policy in other regions isn’t studied at all